Thermostability enhancement of the Pseudomonas fluorescens esterase I by in vivo folding selection in Thermus thermophilus. Issue 1 (1st October 2019) - Mate, Diana M.; Rivera, Noé R.; Sanchez‐Freire, Esther; Ayala, Juan A.; Berenguer, José; Hidalgo, Aurelio
Abstract: Prolonged stability is a desired property for the biotechnological application of enzymes since it allows its reutilization, contributing to making biocatalytic processes more economically competitive with respect to chemical synthesis. In this study, we have applied selection by folding interference at high temperature in Thermus thermophilus to obtain thermostable variants of the esterase I from Pseudomonas fluorescens (PFEI). The most thermostable variant (Q11L/A191S) showed a melting temperature ( T m ) of 77.3 ± 0.1°C (4.6°C higher than the wild‐type) and a half‐life of over 13 hr at 65°C (7.9‐fold better than the wild‐type), with unchanged kinetic parameters. Stabilizing mutations Q11L and A191S were incorporated into PFEI variant L30P, previously described to be enantioselective in the hydrolysis of the (−)‐enantiomer of the Vince lactam. The final variant Q11L/L30P/A191S showed a significant improvement in thermal stability ( T m of 80.8 ± 0.1°C and a half‐life of 65 min at 75°C), while retaining enantioselectivity ( E > 100). Structural studies revealed that A191S establishes a hydrogen bond network between a V‐shaped hairpin and the α/β hydrolase domain that leads to higher rigidity and thus would contribute to explaining the increase in stability. Abstract : Prolonged stability is a desired property for the biotechnological application of enzymes since it allows its reutilization, contributing to making biocatalytic processes more economically competitive with respect to chemical synthesis. In this study, we have applied selection by folding interference at high temperature in Thermus thermophilus to obtain thermostable variants of the esterase I from Pseudomonas fluorescens (PFEI). The most thermostable variant (Q11L/A191S) showed a melting temperature ( T m ) of 77.3 ± 0.1°C (4.6°C higher than the wild‐type) and a half‐life of over 13 hr at 65°C (7.9‐fold better than the wild‐type), with unchanged kinetic parameters.